Physiological-Based Difficulty Assessment for Virtual Reality Rehabilitation Games - Rodrigues, Pedro (2023)
Funding Information: This work is supported by Fundação para a Ciência e Tecnologia (FCT), under HEI-Lab R&D Unit (UIDB/05380/2020) and Project PlayersAll: media agency and empowerment (EXPL/COM-OUT/088 2/2021). Publisher Copyright: © 2023 Owner/Author.